Kajian Estetika dan Unsur Pendukungnya pada Keraton Surakarta - Imam Santosa (Journal of Visual Art and Design, 2007)
In Javanese culture, the Keraton of Surakarta Hadiningrat (Surakarta Hadiningrat Palace) is classified as one of the highly valued Javanese historical objects. It is due to the fact that the history of the Palace's construction has a close connection with the history of the previous Javanese kingdoms, especially those belong to the Mataram Rajakula (dynasty) which was established in the year 1508 of Javanese calendar (Saka) or 1582 AD. The word "keraton" originates from the word 'ke-ratu-an, a manifestation of highly valued  creation or 'Pamesu Budi' (in Javanese language) of a king, his men of letters, and his artists, the creation that caters the Javanese life values and norms. From its meaning, the design of the Surakarta palace"“in Javanese language--characterizes the following: nyipati wewangun toto lahir, sinartan dhamang dumateng pagedhong pikajeng, manunggaling kang agal lan alus, whose translation says that the merger between physical and metaphysical thing, between logic and non-logic, between the soft and hard, and between wadaq and thought.